PENGARUH LEVERAGE, CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR KEUANGAN SUB SEKTOR PERBANKAN PERIODE 2017 - 2021 - Muhamad Rifaldi Tanjung; Muhammad Nuryatno Amin (Jurnal Ekonomi Trisakti, 2022)
This study aims to test the hypothesis of leverage, corporate governance and profitability on tax avoidance. The independent variables used in this study are leverage, Independent Commissioner, Institutional Ownership, Audit Committee, and profitability. The dependent variable used in this study is Tax Avoidance. The data used is secondary data obtained from the annual reports listed on the Indonesia Stock Exchange website and the websites of each company's Financial Sector, Banking Sub-Sector for the period 2017-2021. In this study, 46 companies with 230 data were processed into samples. The sampling method used purposive sampling method. This research uses multiple linear regression analysis method. The analytical method used for hypothesis testing is SPSS 25. The results of this study indicate that leverage, independent commissioners, institutional ownership, audit committee and profitability have a positive effect on tax avoidance.